Study of poly (acrylic acid) and lithium tetrafluoroborate/lithium perchlorate based polymer electrolytes / Ngai Koh Sing - Ngai , Koh Sing (2023)
Polymer electrolytes are among the most potential materials used in electrical double layer capacitor and thus the characteristics of these electrolyte exert great impacts on the performance of the electrochemical devices. In this study, four types of poly(acrylic acid)-based electrolytes were synthesized via solvent casting, namely poly(acrylic acid)/lithium tetrafluoroborate, poly(acrylic acid)/lithium tetrafluoroborate/barium titanate, poly(acrylic acid)/lithium perchlorate, and poly(acrylic acid)/lithium perchlorate/barium titanate. The physicochemical properties such as ionic conductivity, structural and thermal stability were evaluated by electrochemical spectroscopy, themogravimetric analysis, X-ray diffraction and fourier transform infrared analysis. Poly(acrylic acid) (PAA) managed to host up to 30 wt.% of LiBF4 and exhibit the highest conductivity of 6.61 × 10-4 S cm-1. The ionic conductivity of 8.95 ×10−4 S cm−1 is obtained after 10 wt.% of BaTiO3 was added in PAA/LiBF4. The incorporation of 10 wt.% LiClO4 in the PAA matrix demonstrated a highest ionic conductivity, which is 2.40 × 10−6 S cm−1. The ionic conductivity of 1.0 × 10−5 S cm-1 was obtained for PAA-LiClO4-BaTiO3 electrolyte. Arrhenius equation was employed to examine the effects of temperature on the ionic conductivity of the polymer electrolytes. The results shown that all the electrolyte systems obey Arrhenius theory where the ionic conductivity is corresponded to the elevation of temperature. The variation of dielectric constant values with frequency in PAA-based electrolyte systems confirm the presence of polarization process at electrode interface. The variation of dielectric constant with frequency is more prominent with the effect of conducting salt or dopant addition. In the addition of more conducting salt into PAA electrolyte matrix, the loss tangent peaks shift towards higher frequency suggesting the speed up of relaxation time. Polymer electrolytes with wide electrochemical stability window (ESW) are potentially to be applied for electrochemical devices. PAA-LiBF4 and PAA-LiBF4-BaTiO3 electrolyte demonstrated ESW at 3.2 V and 4.0 V respectively. However, the electrolyte systems using LiClO4 as conducting salt portrays a wider ESW which are about 10.0 V and 11.5 V for PAA-LiClO4 and PAA-LiClO4-BaTiO3, respectively. The study confirmed that incorporation of conducting salt of LiBF4/LiClO4 and BaTiO3 improves the thermal stability of polymer electrolyte. The XRD study indicates that higher loading of LiBF4/LiClO4 and BaTiO3 indicates a higher degree in amorphous nature which improves the ionic conductivity in the PAA electrolytes. The FTIR study showed evident on the interaction between Li+ and PAA. The characterization study indicates that all the polymer electrolyte prepared in my study can be used as promising electrolyte materials for EDLC application especially the PAA-LiClO4 based electrolytes with excellence electrochemical stability window.